“We Seem to Have Always Spoken in Prose . . .” Policy Analysis Is a Clinical Profession: Implications for Policy Analysis Practice and Instruction. - Geva-May, Iris (Policy Studies Journal, 2007)
The purpose of this article is (i) to propose the concept of policy analysis as a clinical profession, (ii) to relate to the clinical intellectual processes involved in policy analysis, and (iii) following studies in other clinical disciplines, to infer implications for policy analysis and policy analysis instruction. The article will highlight notions of clinical reasoning and clinical cognitive processes relevant to policy analysis and will address reasoning errors associated with bounded rationality and uncertainty in the clinical analytic process. The article seeks to promote awareness of clinical notions and of their relevance for policy analysis practice and instruction. Reprinted by permission of the publisher.